Green Bean Juice (Phaseolus radiatus linn) Decrease Total Cholesterol Levels In Women With Hypercholesterolemia - Choirun Nissa; Indah Asrifah; Dian Kartika Ratnasari (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Cholesterol total level is a risk factor for cardiovascular disease. Mung beans contain soluble fiber and isoflavones that decrease cholesterol levels. The aim of this research is to find out the potency of mung beans juice to decrease total cholesterol total level of hypercholesterol woman. Research design was quasi experimental with pretest - posttest control group. The subjects were 34 women with hypercholesterolemia, and divided into two groups ie 17 womens in Penarukan Village which is treatment group and 17 womens in Ketapang Village which is control groups. All the subjects have met the inclusion criteria. The treatment group consumed juice of 300 ml/day for 14 days while the control group did not get juice. It was a single blind treatment. Cholesterol total level measurement used Electrode Based Biosensor and CHOD-PAP methods. The mean of cholesterol total level of control group before and after was increasing 5,7% ie 240,1 mg/dl and 253,9 mg/dl, but intervention group was decreasing 11% ie 220 mg/dl and 195,7 mg/dl. Paired t-test result shows that there is a significant difference between total cholesterol levels before and after in the treatment group and control group (p= 0.000). The conclusion of this research is the provision of mung beans juice 300 ml/day for 14 days reduce total cholesterol levels. Keywords : Hypercholesterolemia Women; Mung beans Juice; Total Cholesterol Level;